ANALISIS PERHITUNGAN HARGA POKOK SEWA KAMAR BERDASARKAN ACTIVITY BASED COSTING SYSTEM PADA HOTEL RANGGONANG SEKAYU - Deswati Supra (Jurnal Ilmiah Akuntansi Rahmaniyah, 2020)
This study aims to determine the calculation of the room cost using the Activity Based Costing System at the Ranggonang Hotel. The data source used by the writer in this study is secondary data. In this study the writer used qualitative and quantitative analysis techniques. The results showed that the Ranggonang Sekayu Hotel was not suitable to use the ABC method in calculating the cost of room rent. This is because the cost of room rent using the ABC method is greater which will have an impact on the high room rental rates at the Ranggonang Sekayu Hotel.